Fragment of an Unpublished Manuscript by John Rae (1796-1872) - Mixter, C. W. (Quarterly Journal of Economics, 1901)
Journal Article Fragment of an Unpublished Manuscript by John Rae (1796–1872) Get access The Quarterly Journal of Economics, Volume 16, Issue 1, November 1901, Pages 123–125, https://doi.org/10.2307/1882907 Published: 01 November 1901